2012
DOI: 10.2478/cttr-2013-0918
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Dihydroxybenzenes in Cigarette Smoke. Part 1. Contribution from Chlorogenic Acid and Rutin

Abstract: Catechol and alkylcatechols are known co-carcinogens present in cigarette smoke. Hydroquinone, although nongenotoxic, can form a metabolite with nephrotoxic properties and is a potential human carcinogen. The formation of dihydroxybenzenes during smoking originates with the pyrolysis of several precursors from tobacco. These include cellulose, chlorogenic acid, rutin, etc. The present study attempts to quantitate the contribution of chlorogenic acid and rutin to the formation of dihydroxybenzenes and of some a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 15 publications
2
7
0
2
Order By: Relevance
“…This present study describes the contribution of tobacco quinic acid (or (1S,3R,4S,5R)-1,3,4,5-tetrahydroxycyclohexanecarboxylic acid) and myo-inositol (or (1R,2R,3S,4S,5R,6S)-cyclohexane-1,2,3,4,5,6-hexol) to the formation of dihydroxybenzenes in cigarette smoke. The study is a continuation of a previous one showing the contribution of chlorogenic acid and rutin as precursors for these compounds (6). The yields of dihydroxybenzenes formed by pyrolysis of quinic acid and myo-inositol are relatively high and both quinic acid and myo-inositol can be present in some tobacco types at levels as high as 1% by weight.…”
mentioning
confidence: 60%
See 4 more Smart Citations
“…This present study describes the contribution of tobacco quinic acid (or (1S,3R,4S,5R)-1,3,4,5-tetrahydroxycyclohexanecarboxylic acid) and myo-inositol (or (1R,2R,3S,4S,5R,6S)-cyclohexane-1,2,3,4,5,6-hexol) to the formation of dihydroxybenzenes in cigarette smoke. The study is a continuation of a previous one showing the contribution of chlorogenic acid and rutin as precursors for these compounds (6). The yields of dihydroxybenzenes formed by pyrolysis of quinic acid and myo-inositol are relatively high and both quinic acid and myo-inositol can be present in some tobacco types at levels as high as 1% by weight.…”
mentioning
confidence: 60%
“…The experiments performed in this study are similar to those previously reported for the evaluation of the contribution of tobacco chlorogenic acid and rutin to smoke dihydroxybenzenes formation (6). It consisted of three different types of experiments.…”
Section: Methodsmentioning
confidence: 82%
See 3 more Smart Citations